Identification of aflatoxin biosynthesis genes by genetic complementation in an Aspergillus flavus mutant lacking the aflatoxin gene cluster. - Prieto, R (1996)
Aspergillus flavus mutant strain 649, which has a genomic DNA deletion of at least 120 kb covering the aflatoxin biosynthesis cluster, was transformed with a series of overlapping cosmids that contained DNA harboring the cluster of genes. The mutant phenotype of strain 649 was rescued by transformation with a combination of cosmid clones 5E6, 8B9, and 13B9, indicating that the cluster of genes involved in aflatoxin biosynthesis resides in the 90 kb of A. flavus genomic DNA carried by these clones. Transformants 5E6 and 20B11 and transformants 5E6 and 8B9 accumulated intermediate metabolites of the aflatoxin pathway, which were identified as averufanin and/or averufin, respectively.These data suggest that avf1, which is involved in the conversion of averufin to versiconal hemiacetal acetate, was present in the cosmid 13B9. Deletion analysis of 13B9 located the gene on a 7-kb DNA fragment of the cosmid. Transformants containing cosmid 8B9 converted exogenously supplied O-methylsterigmatocystin to aflatoxin, indicating that the oxidoreductase gene (ord1), which mediates the conversion of O-methylsterigmatocystin to aflatoxin, is carried by this cosmid. The analysis of transformants containing deletions of 8B9 led to the localization of ord1 on a 3.3-kb A. flavus genomic DNA fragment of the cosmid.